Enhanced titanium dioxide photocatalyst embolized on micropores silicon wafer: An experimental approach - Basheer, Esmail Abdullah Mohammed; Abdulbari, Hayder A.; Mahmood, Wafaa K. (Society of Chemical Industry, 2020)
BACKGROUND: The wide bandgap and low activity under visible light of titanium dioxide (TiO2) have limited its use in many industrial processes. This limitation is associated with the inadequate solar spectrum that activates its surface, where most of the photoexcited electron–hole pairs recombine thus, leading to a drop in the photocatalytic performance. Immobilization of TiO2 on the surface of other materials such as silicon is a suitable approach to overcome these drawbacks. However, the known immobilization methods require either high‐temperature or high‐pressure conditions. The objective of the present work is to introduce and evaluate a low power‐consumption electrodeposition method for creating a new photocatalyst that can act in visible light using electrochemical anodization for immobilizing the TiO2 on a silicon wafer surface. Two methods were utilized for immobilization which is electrodeposition and sol–gel. The prepared photocatalyst surface and composition were characterized by scanning electron microscopy (SEM), energy‐dispersive X‐ray spectroscopy (EDX), X‐ray diffraction (XRD), and X‐ray photoelectron spectroscopy (XPS).